"Efecto de la nutrición translaminar sobre el rendimiento del banano (Musa AAA) variedad williams cantón Valencia, los Ríos". - Tello Martínez, Víctor Manuel (2020)
The present research aims to evaluate the effect of translaminar fertilization on the yield in the banana crop (Musa AAA.), Determining the cost-benefit relationship with the application of translaminar fertilizer, in the banana crop (Musa AAA.) and identify the dose of fertilizer, which helps to obtain the highest number of boxes per bunches harvested. The test was carried out at the “San Carlos Chillovado” farm owned by Mr. Carlos Pérez, Valencia canton, it is located in the north of the Province of Los Ríos Km 13 via Quevedo. A completely randomized design (DCA) was used. They were fertilized every 30 days in all treatments with 100 mL of the fertilizer, once the appearance of the acorn or reproductive development stage occurred. According to the variable bunch weight according to the ANOVA analysis of variance. In the variable bunch weight, there were no statistical significance, therefore, if there were numerical differences in the treatments with a higher average in T2 with 28.86 Kg, as opposed to T3 with an average of 24.25 Kg lower weights. Regarding the variable boxes per hectare, there were no statistical significance between the treatments, where there was a great numerical difference in the treatments, giving a higher average T6 1.67 boxes per bunch harvested which T5 obtained 1.19 boxes being lower than the other treatments. According to the cost benefit relation variable in the results obtained, treatment T1 obtained a cost benefit relation of 8.13 using a dose of 20 mL with a frequency of 30 days being higher than the others, which treatment T0 obtained a cost benefit relation of 1.18 with an edaphic fertilization inferior to the others. Keywords: Translaminar, inflorescence, cost benefit ratio.